Pengembangan Aplikasi Perangkat Bergerak Sebagai Media Pemantau Kesehatan Terhadap Penyakit Hipertensi - Giovanka Bisano Putra; Lutfi Fanani; Adam Hendra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Hypertension is a blood pressure disease which blood pressure value is above normal. Hypertension may caused by age, work, lifestyle such as smoking, and blood pressure. The number of deaths from hypertension reaches 6% of the death population at all ages in Indonesia. From these problems, a system called Blood Care was created. The Blood Care application is a system that scans blood pressure through the fingertips of users using image processing. The results of the blood pressure will be processed further using the naive bayes method to obtain a calculation risk for hypertension. After data the data such as hypertension risk and blood pressure occur, that data will be stored in Firebase. In the naive Bayes method, researchers have 5 features and 2 classes for classification. Blood Care software development was carried out using software development life cycle prototyping and in this software, four types of testing were carried, there are validation, unit, usability, and accuracy testing. From the tests that have been conducted, the results show that all functionality has been successfully implemented, all function has worked well according to every case that may happened in the function, and the usability value of the application reaches 81,5 and the accuracy of the Blood Care application is 87,5%.